CCAFS Gender Survey – Nicaragua Climate Smart Village - International Center for Tropical Agriculture; International Food Policy Research Institute (2017)
The purpose of this baseline survey is to gather gender-disaggregated data on agricultural activities, decision-making, weather information, risk-perception and values from rural households in the Climate Smart Village in Tuma la Dalia, Nicaragua. This intra-household survey collects information related to household characteristics, farm production, decision-making, CSA adoption, access to agro-climate information services, etc. from both male and female respondents. This information will be used for researchers, policy-makers and development practitioners to better understand the vulnerabilities of men and women to climate change, how they differ, and what actions can be taken to reduce that vulnerability. (2016-12-18)